Chapter Signorie rurali e poteri superiori in Italia settentrionale (secoli XIV-XV) - Del Tredici, Federico (Firenze University Press, 2023)
The essay focuses on the relationship between states and rural lordships in northern Italy in the late Middle Ages. Two main questions lie at the core of the investigation: on the one hand, the influence exerted by central authorities on how seigneurial power was performed, legitimised, and transmitted; on the other hand, the role acquired by rural lordships in the organisation of the various states. In both cases the highest attention is paid to the different origins of seigneurial experiences, which still played a crucial part at the end of the Middle Ages in determining the chances of survival of lordships, the lords’ political role, and their prerogatives over subjects.